Reading Freud : explorations & entertainments - Gay, Peter, 1923-2015 (Yale University Press, 1990)
Gay presents a series of essays ranging from reflections on Freud and Shakespeare to Gay's controversial spoof review of Freud's The Interpretation of Dreams.